Efficiency improvement of green light-emitting diodes by employing all-quaternary active region and electron-blocking layer. (January 2018) - Usman, Muhammad; Saba, Kiran; Han, Dong-Pyo; Muhammad, Nazeer
Abstract: High efficiency of green GaAlInN-based light-emitting diode (LED) has been proposed with peak emission wavelength of ∼510 nm. By introducing quaternary quantum well (QW) along with the quaternary barrier (QB) and quaternary electron blocking layer (EBL) in a single structure, an efficiency droop reduction of up to 29% has been achieved in comparison to the conventional GaN-based LED. The proposed structure has significantly reduced electrostatic field in the active region. As a result, carrier leakage has been minimized and spontaneous emission rate has been doubled. Highlights: The proposed light-emitting diode structure demonstrates improved efficiency in light-emitting diodes. Improving the efficiency of light-emitting diodes is always a need of the community and our results demonstrate the same. The proposed structure is one of its kind and is presented as a solution to 'green gap' issue faced by the community.